Identifikasi Jenis Makroalga di Pantai Pandanan Kabupaten Lombok Utara - Sucika Armiani; Baiq Muli Harisanti; Ismail Efendi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Besides being a tourist destination, Pandanan Beach has considerable marine potential. One of the marine potentials that is still minimally utilized in this location but has strategic value is macroalgae. This study aims to identify the types of macroalgae found in Pandanan Beach, North Lombok Regency. The type of research used is descriptive research that describes the types of macroalgae around Pandanan Beach. Determination of the research location used a purposive sampling method at 3 stations with a distance between stations of 10 meters. Sampling was carried out using a 1 m × 1 m quadrant, while the distance between the quadrants was determined using a 100 meter line transect. Samples obtained along the transect were then put into plastic bags and given a 75% alcohol solution for further identification. The identification results showed that there were 16 types of macroalgae in Pandanan Beach. These species fall into three divisions: Chlorophyta (6 species) (Chaetomorpha crassa, Halimeda macroloba, Halimeda monile, Boergesenia forbesii, Dictyosphaeria versluysii, and Ulva intestinalis), Phaeophyta (5 species) (Padina australis, Turbinaria decurrens, Sargassum polycystum, Hydroclathrus sp., and Dictyota sp.), and Rhodophyta (5 species) (Eucheuma sp., Gracilaria verrucosa, Galaxaura arborea, Laurencia papillosa, and Gelidium spinosum).